Análise dos programas habitacionais em Santa Maria: o caso do Conjunto Habitacional Tancredo Neves - Rubin, Graziela Rossatto (2013)
This dissertation aims to discuss the housing problem in the urban space of Santa Maria, specifically to analyze how the conformation and the implantation of Tancredo Neves housing complex happened. This complex was the biggest enterprise built in this city by Companhia Habitacional do Rio Grande do Sul (COHAB RS), together with Banco Nacional de Habitação (BNH) as the funding body. To understand the housing production process in Tancredo Neves neighborhood, we have done a historical and bibliographic review of housing in Brazil, in Rio Grande do Sul and in Santa Maria. We have also performed a field work with interviews and data collection related to this housing complex and its dwellers. Originally the area of this complex was a rural area that was misappropriated to build this complex. It is located 10 km from downtown and when it was built it was a sparsely populated area. Tancredo Neves housing complex was originally composed of 3184 dwellings, being 2608 houses in individual grounds and 36 buildings with 16 apartments each. Since the beginning, water and sewer supply network and recreation, institutional and commercial areas were provided. Since it was built, a lot of changes occurred in Tancredo Neves and, nowadays, this place is quite prosperous and developed, with strong trading and job offers to local population. Furthermore, a lot of dwellers work at this neighborhood because job offers have grown. At the present, this complex belongs to Tancredo Neves neighborhood (with approximately 11500 inhabitants) together with Piratini allotment, Vila Canaã and a big area with striking features of rural properties. Changes occurred there, and some important are land-use and housing morphology due to dwellers needs, such as bigger houses and more commercial places. The number of these commercial places and the size of the houses are bigger than it was previously predicted. We can observe this in the terrains, which are almost totally occupied. Thus, the most surprising result was that the initial idea that the place was needy of infrastructure was wrong, because with this research we can see that Tancredo Neves dwellers are very satisfied living there and many people do not even think about moving to other neighborhoods or downtown.